ANALISIS PERMINTAAN TENAGA KERJA PADA INDUSTRI KECIL DAN MENENGAH DI KABUPATEN LAMONGAN TAHUN 2009-2013 - Afriliyanti Ismei; Andri Wijanarko; Henny Oktavianti (MediaTrend, 2015)
Economic development on a nation is possibly conducted by increasing the growth on industrial sectors. Job opportunities in medium and big industry is considered less than it is compared with the small and the medium industries. It is happened because the big and medium industries applies capital intensive. Labor average Reduction per small and medium industries on Lamongan region is significantly decreasing in the last two years. If the next year shows the reduction on the number of labor, so the employment is not conducted optimally since the small and medium industries play and important role in employment. The purpose of the study is to determine the influence of industrial total number, investment and production value on employment in small and medium industrial of Lamongan Region in 2009 – 2013. Analysis method applied is panel data method which is used to determine the number of industries, investment and production value hypothesis on small and medium industry’s labor demand in 2009–2013. The result of study shows that the number of industries, investment and production value variable have positive influence and significance on small and medium industry’s labor demand at Lamongan Region in 2009 – 2013. The conclusion of study shows that the overall independent variables (number of industries, investment and production value) all together and simultaneously influence the dependent (labor demand on small and medium industries) variable at Lamongan Region in 2009 – 2013.